Pengaruh Rasio Keuangan Terhadap Financial Distress (Studi Kasus Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021 -2023) - Rachman, Fahmia Nur Fitria; Mardani, Ronny Malavia; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Financial distress is a condition in which a company experiences a financial crisis and is unable to meet its obligations. This condition is characterized by a significant decline in profits, fixed assets, and other financial indicators over several periods, which often serve as early indicators of bankruptcy. The purpose of this study is to determine the effect of liquidity, profitability, leverage, activity, and sales growth on financial distress. The method used in this study is purposive sampling with predetermined criteria. The sample size used was 108 manufacturing companies in the food and beverage sub-sector, in accordance with the established criteria. In this study, the research method used was quantitative with secondary data collection. Secondary data was obtained from the annual financial reports of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The data analysis technique used was multiple linear regression analysis with the program used being Eviews12. Based on the results of this study, it can be concluded that liquidity, profitability, leverage, and activity ratios have a significant effect on financial distress. The sales growth ratio has no effect on financial distress. Keywords: Financial Distress, Liquidity, Profitability, Leverage, Activity, Sales Growth